Accumulation and speciation of arsenic in Eisenia fetida in sodium arsenite spiked soils - A dynamic interaction between soil and earthworms. (April 2023) - Xing, Weiqin; Geng, Hongpei; Wang, Yali; Zhao, Linlin; Yang, Yongqiang; Wang, Yale; Tian, Shuhang; Cao, Yongxin; Zhang, Zhe; Li, Liping
Abstract: Arsenic (As) is a toxic metalloid that is a significant global pollutant of the environment and a persistent bioaccumulation carcinogen. Earthworms are frequently employed as sentinel organisms to investigate the bioavailability of As in contaminated soils. However, the process of As accumulation in earthworms and the mechanism of transformation of As species in their bodies are not well understood. The accumulation of As and variation of As species in the earthworms ( Eisenia fetida ) exposed to sodium arsenite (0, 20, and 80 mg kg −1 As) were investigated in this study. The total As concentration of earthworms in the three treatments at various sample times was dose-dependent on soil As content. After 56 days of exposure, the high concentration treatment had the highest total As content (772 ± 21 mg kg −1 ) in earthworms, followed by the low concentration treatment (579 ± 42 mg kg −1 ) and control (31 ± 1 mg kg −1 ). During 56 days, the proportion of trivalent As in earthworms increased from 70% to more than 90%, while pentavalent As decreased by 11–18%. On day 28, the sum of the four organic As species reached a maximum (<1%). Changes in soil As species and an increase in bioavailable As cause earthworms to accumulate more As. The total As in soil after 56 days of exposure was 9.51 ± 0.50, 25.6 ± 0.60, and 82.8 ± 0.28 mg kg −1, which was not significantly different from the total As in soil before the experiment. These findings are useful in assessing the risk of earthworm exposure to sodium arsenite in the soil. Graphical abstract: Image 1 Highlights: Total As concentration in earthworms was dose-dependent on soil As content. The trivalent arsenic increased and pentavalent arsenic decreased in earthworms. The sum of the four organic As species reached a maximum (<1%). The more soil Av-As and Olsen-P, the more As accumulated by earthworms.